Knowledge in Manuscript Writing and Readiness to Conducting Research among Selected Accounting Students - John Mark Asio (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the knowledge of manuscript writing and the readiness among selected accounting students to conduct research from a tertiary institution in Olongapo City, Philippines. The study used a descriptive-correlation research design to 70 purposively chosen students. The data underwent descriptive and inferential measures with the help SPSS 23 software. The study found that students were